PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI KECAMATAN GIRIAN KOTA BITUNG (Studi Tentang Pelayanan Akte Jual Beli) - Tomuka, Shinta (Sam Ratulangi University, 2013)
Applying of governance good to represent absolute requirement of people majority for the shake of creation an political system more standing up for governance importance of people as according to principles democratize universally. This matter earn also become factor impeller of its form governance political wanting that various process governance of that goodness from facet process formulation of policy of public, management of development, execution of public bureaucracy of governance to be walking transparently, efficient and effective to increase kesejahtraan of people. Writer conduct research about principal applying of Governance Good in execution of service of Public in District Of Girian Town of Bitung (study about service of Akte Sales). This research will use method qualitative, that is a[n research of kontekstual making human being as instrument, and adapted for by fair situation that in its bearing with data collecting which is on generally have the character of qualitative. Approach qualitative distinguished by target of research coping to comprehend symptoms which in such a manner which do not need kuantifikasi, because symptom do not enable to be measured precisely. Focus in this research : 1) governmental Principle Participation government officer in giving service of public; 2) Rule / definitive order in service of Sale Act Buy; 3) Principle Transparency in service of making of Sale act Buy; and 4) Principal and Responsive Principle of Akuntabilitas. Keywords : Principles Applying, Good Governance, Public Service